High resolution of colour vision, but low contrast sensitivity in a diurnal raptor. Issue 1885 (29th August 2018) - Potier, Simon; Mitkus, Mindaugas; Kelber, Almut
Abstract : Animals are thought to use achromatic signals to detect small (or distant) objects and chromatic signals for large (or nearby) objects. While the spatial resolution of the achromatic channel has been widely studied, the spatial resolution of the chromatic channel has rarely been estimated. Using an operant conditioning method, we determined (i) the achromatic contrast sensitivity function and (ii) the spatial resolution of the chromatic channel of a diurnal raptor, the Harris's hawk Parabuteo unicinctus . The maximal spatial resolution for achromatic gratings was 62.3 c deg −1, but the contrast sensitivity was relatively low (10.8–12.7). The spatial resolution for isoluminant red-green gratings was 21.6 c deg −1 —lower than that of the achromatic channel, but the highest found in the animal kingdom to date. Our study reveals that Harris's hawks have high spatial resolving power for both achromatic and chromatic vision, suggesting the importance of colour vision for foraging. By contrast, similar to other bird species, Harris's hawks have low contrast sensitivity possibly suggesting a trade-off with chromatic sensitivity. The result is interesting in the light of the recent finding that double cones—thought to mediate high-resolution vision in birds—are absent in the central fovea of raptors.